2022
DOI: 10.1364/prj.443706
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Brillouin scattering in chiral photonic crystal fiber

Abstract: Optical non-reciprocity, which breaks the symmetry between forward and backward propagating optical waves, has become vital in photonic systems and enables many key devices, such as optical isolators, circulators and optical routers. Most conventional optical isolators involve magneto-optic materials, but devices based on optical nonlinearities, optomechanically induced transparency and stimulated Brillouin scattering (SBS) have also been demonstrated. So far, however, they have only been implemented for linea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…In general, the twist rate must be high enough to produce a circular birefringence that overcomes inevitable deviations from perfect N -fold rotational symmetry in the PCF structure. Although, in principle, a perfect untwisted C N PCF will support pure circularly polarized vortex modes, in practice, these modes are highly sensitive to inevitable small structural imperfections that vary along the fiber, causing interpolarization coupling ( 20 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the twist rate must be high enough to produce a circular birefringence that overcomes inevitable deviations from perfect N -fold rotational symmetry in the PCF structure. Although, in principle, a perfect untwisted C N PCF will support pure circularly polarized vortex modes, in practice, these modes are highly sensitive to inevitable small structural imperfections that vary along the fiber, causing interpolarization coupling ( 20 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the wave vector selection rules of spontaneous Brillouin scattering can be modified in microstructures . Also, the scattering cross sections can be largely enhanced by means of micro- and nanostructures, such as microcavities , and surfaces. , More recently, polarization control in stimulated Brillouin scattering has been reported in birefringent photonic crystal fibers, polarization maintaining fibers, and nanofibers. It is intriguing to explore the control of polarization in the spontaneous Brillouin scattering regime in microstructures which is otherwise subtle to observe in fibers. In this work, we show that not only the wave vector selection rules and scattering cross sections but also the polarization selection rules of spontaneous Brillouin scattering can be strongly modified in polarization-sensitive photonic resonators, such as elliptical micropillars, , optical nanoantennas, and metasurfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of chiral (PCF) [12] -a unique platform for studying the behavior of light in chiral structures that are infinitely extended in the direction of the twist-has enabled investigation of SBS process in the presence of chirality. [13] Here we report a vortex Brillouin fiber laser in which chiral PCF is used to robustly preserve circularly polarized vortex modes over long distances, permitting topology-selective Brillouin gain. [14] In particular, angular momentum conservation dictates that the topological charge and spin of the backward Brillouin signal are opposite in sign to those of the pump.…”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of chiral (PCF) [ 12 ] —a unique platform for studying the behavior of light in chiral structures that are infinitely extended in the direction of the twist—has enabled investigation of SBS process in the presence of chirality. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%